Factors Related to Nutritional Status in Toddlers in the Bea Mese Health Center Work Area, Cibal District, Manggarai Regency (Pergizi Pangan DPD NTT, 2025)
Background: Indonesia faces the threat of malnutrition with the prevalence of malnutrition, undernutrition, stunting, wasting, and overweight still high, especially in East Nusa Tenggara Province as the area with the highest cases. In Manggarai Regency, the number of cases of malnutrition in toddlers continues to increase from year to year, reaching 320 cases or 1.3% in 2022. Objectives: The aim is to analyze the factors related to the nutritional status of toddlers in the Bea Mese Health Center Working Area, Cibal District, Manggarai Regency. Methods: This study used a quantitative method with a cross-sectional approach. The research sample was 87 mothers who had toddlers with the sampling method used being simple random sampling. Data were analyzed using the chi square test. Results: The results of the study showed that the level of energy adequacy (p=0.013), protein (p=0.000), parenting patterns of providing food in the amount of food (p=0.001), frequency of eating (p=0.001), type of food (p=0.001), parenting patterns of health maintenance (p=0.004), parenting patterns of personal and environmental hygiene (p=0.014) had a significant relationship with malnutrition status, while knowledge (p=0.363) did not have a significant relationship with malnutrition status. Conclusions: There is a relationship between the level of energy adequacy, the level of protein adequacy and maternal parenting patterns with the incidence of malnutrition in toddlers. Meanwhile, maternal nutritional knowledge is not related to the incidence of malnutrition in toddlers.